Permitted Ways of Using Force or Threat by Force under the Conditions of Current International Law - Laura Bačová (Societas et Iurisprudentia, 2020)
This paper aims to provide readers with a comprehensive overview of the current challenges to the rules of the public international law on the use of force. “New wars” or, better to say, armed conflicts are no longer a duel between the rival states, but include a complex mix of internal and international elements, taking place in a globalized environment and involving an increasing number of the state and non-state actors. Recent armed conflicts can be distinguished from conventional wars mostly in terms of their context, roles of the states and non-states actors, their methods, motives, objectives and their victims. There are growing concerns at the failure to respond adequately to modern security threats and humanitarian catastrophes, such as in Rwanda and Syria. Such concerns have led to push the boundaries of the law, seeking to construct a unilateral right to use the force preventively or for humanitarian purposes. The paper examines the concepts of the humanitarian intervention and the responsibility to protect.